Forms of irony in Carl Schmitt's Political Romanticism, The Buribunks and Ex Captivitate Salus. Issue 2 (3rd April 2019) - Manderson, Desmond; Bikundo, Edwin
ABSTRACT: The argument for the role of various crises of modernity in the totalitarian violence of the twentieth century is well known. At the heart, however, of Carl Schmitt's own role in this troubling history, lies a certain irony which complicates the reading, recognition and reckoning of his fearsome and confronting work. This paper aims to remedy that omission. Schmitt deliberately used irony to feign distance from his own deeply held attitudes as expressed and implied both in his work and through his actions. Paradoxically, nothing so foreshadows the Schmitt's intellectual fate than his own critique on the one hand, and embrace, on the other, of the uses and misuses of irony.